2005
DOI: 10.1074/jbc.m501080200
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Inhibits Adipogenesis through β-Catenin-dependent and -independent Mechanisms

Abstract: Wnt signaling has been reported to block apoptosis and regulate differentiation of mesenchymal progenitors through inhibition of glycogen synthase kinase 3 and stabilization of ␤-catenin. The effects of Wnt in preadipocytes may be mediated through Frizzled (Fz) 1 and/or Fz2 as these Wnt receptors are expressed in preadipocytes and their expression declines upon induction of differentiation. We ectopically expressed constitutively active chimeras between Wnt8 and Fz1 or Fz2 in preadipocytes and mesenchymal prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
163
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(174 citation statements)
references
References 51 publications
11
163
0
Order By: Relevance
“…Drosophila Kc167 cells were routinely cultured as described (10). Mouse ST2 marrow-derived stromal cells were cultured and induced to differentiate into adipocytes as described (27). To visualize lipid accumulation, cells were stained with Oil Red-O 6 days after induction of differentiation (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drosophila Kc167 cells were routinely cultured as described (10). Mouse ST2 marrow-derived stromal cells were cultured and induced to differentiate into adipocytes as described (27). To visualize lipid accumulation, cells were stained with Oil Red-O 6 days after induction of differentiation (26).…”
Section: Methodsmentioning
confidence: 99%
“…5B). Mutation of either site alone gave only a partial rescue, suggesting that both sites are functionally important (data not shown We chose to study these mammalian miR-8 family members in ST2 marrow stromal cells because it has been shown that Wnt signaling potently inhibits the differentiation of ST2 cells into adipocytes (25)(26)(27). Suppression of endogenous Wnt signaling in ST2 cells promotes adipogenesis, and ectopic treatment with Wnts blocks the differentiation process (data not shown) (25).…”
Section: Mir-8 Directly Targets Cg32767 a Positive Regulator Of The Wgmentioning
confidence: 99%
“…This effect appears to be mediated by BMP-dependent effects on the Wnt signaling pathway. Wnt signaling controls commitment of mesenchymal progenitors to the osteoblastic lineage and stimulates the expression of the osteoclast inhibitor OPG (Glass et al 2005;Hill et al 2005;Kennell and MacDougald 2005;Rodda and McMahon 2006;Kamiya and Mishina 2011;Baron and Kneissel 2013). Wnt activating gene mutations cause high bone mass, whereas inactivating mutations cause osteopenia characterized by severely reduced bone mineral density (Gong et al 2001;Boyden et al 2002;Little et al 2002;Patel and Karsenty 2002;Babij et al 2003;Winkler et al 2003).…”
Section: Tgf-b Family Signaling In Connective Tissuesmentioning
confidence: 99%
“…As an inhibitor of WNT signalling, DKK1 can be expected to promote adipogenesis, since active WNT signalling prevents both precursor cells from entering the adipose lineage and the normal differentiation of committed pre-adipocytes [11][12][13]. DKK1 binds to both Kremen and the LRP receptor, thus preventing WNT from binding and activating the WNT signal [14].…”
Section: Introductionmentioning
confidence: 99%